Hubungan Antara Persepsi, Dukungan Suami, Dan Tingkat Penghasilan Dengan Pemilihan Jenis Kontrasepsi Di Desa Jetak Kecamatan Sidoharjo Kabupaten Sragen - Mutti'ah, Lissa; , Yuli Kusumawati, SKM., M. Kes (Epid); , Kusuma Estu Werdani, SKM., M.Kes (2014)
The rate of population growth in Indonesia's high will affect the standard of living and welfare of the population, an attempt to decrease the number of residents with family planning programs, and advocate couple of fertile age using contraceptives. The purpose of this study is to describe and analyze the relationship between perception , her husband support and the level of income with the selection of contraceptives in the Jetak village, Sidoharjo District of Sragen. This research is survey observational research with cross sectional approach. The population of this research all women of childbearing age couples in the village as much as 1,144 people Jetak. The samples are 113 which decided by Proportional stratified random sampling technique. The statistic testing technique used Chi Square test. The results of this research shows that there is a relationship between perception (p = 0.037), and the support of her husband (p = 0.017) with the selection of contraception, but there is no relationship between the level of income (0,307) with the selection of contraceptives in the Jetak village, Sidoharjo District of Sragen Region